2017
DOI: 10.1038/s41598-017-04333-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia is a Key Driver of Alternative Splicing in Human Breast Cancer Cells

Abstract: Adaptation to hypoxia, a hallmark feature of many tumors, is an important driver of cancer cell survival, proliferation and the development of resistance to chemotherapy. Hypoxia-induced stabilization of hypoxia-inducible factors (HIFs) leads to transcriptional activation of a network of hypoxia target genes involved in angiogenesis, cell growth, glycolysis, DNA damage repair and apoptosis. Although the transcriptional targets of hypoxia have been characterized, the alternative splicing of transcripts that occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 81 publications
4
61
1
1
Order By: Relevance
“…A recent study showed that breast cancer cells underwent extensive changes in AS if cultured in hypoxic conditions. Specifically, RNAseq data showed predominant intron retention events (among others, targets of AS included LDHA, TNFSF13, and ARHGAP4 for intron retention, MARCH7, PCBP2, and LRCH3 for exon skipping, and VGLL4, AHNAK, and NFE2L1 that are subjected to alternative first exon usage) [106]. A similar study also confirmed the occurrence of specific AS events during hypoxia in a cellular model of hepatoma [107].…”
Section: As: An Important Player During Metabolic Stress and Neo-angisupporting
confidence: 54%
“…A recent study showed that breast cancer cells underwent extensive changes in AS if cultured in hypoxic conditions. Specifically, RNAseq data showed predominant intron retention events (among others, targets of AS included LDHA, TNFSF13, and ARHGAP4 for intron retention, MARCH7, PCBP2, and LRCH3 for exon skipping, and VGLL4, AHNAK, and NFE2L1 that are subjected to alternative first exon usage) [106]. A similar study also confirmed the occurrence of specific AS events during hypoxia in a cellular model of hepatoma [107].…”
Section: As: An Important Player During Metabolic Stress and Neo-angisupporting
confidence: 54%
“…Splicing analysis was performed using in-house bioinformatic pipeline 68,69 . Briefly, mapped reads were filtered and classified into the following three groups based on their distance and location around the annotated splice sites: (1) reads mapped to exon-exon junctions, (2) reads bridging exon-intron junctions, and (3) reads mapped completely to introns.…”
Section: Methodsmentioning
confidence: 99%
“…The reads in groups 1 and 2 were used for the calculation of SI for each splice site for the selection of potential differential splicing candidates. To identify the various types of splicing events, including exon skipping, intron retention, and alternative splice sites, the SI calculation was adjusted for each type of splicing events 68 . All potential splicing candidates were classified into either known/annotated alternative splicing or novel splicing events that are not represented in the annotation library, and were assessed by Fisher's exact test and SI change.…”
Section: Methodsmentioning
confidence: 99%
“…One important cause for concern is the repeated occurrence of regulators and pathways that suggest neoplastic disorders. Upregulation of glycolysis, which was observed as the primary pathway classifier in the same-background comparison is considered a "near-universal property" of primary and metastatic cancers [39][40][41][42]. Oxidative stress and impaired glycolysis can both arise due to mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%